Correlative distribution of DOM and heavy metals in the soils of the Zhangxi watershed in Ningbo city, East of China. (15th April 2022) - Wang, Zhe; Han, Ruixia; Muhammad, Azeem; Guan, Dong-Xing; Zama, Eric; Li, Gang
Abstract: In peri-urban critical zones, soil ecosystems are highly affected by increasing urbanization, causing probably an intense interaction between dissolved organic matter (DOM) and heavy metals in soil. Such interaction is critical for understanding the biogeochemical cycles of both organic matter and heavy metals in these zones. However, limited research has reported the correlative distribution of DOM and heavy metals at high seasonal and spatial resolutions in peri-urban critical zones. In this study, 160 soil samples were collected from the farmland and forestland of Zhangxi watershed, in Ningbo, eastern China during spring, summer, fall and winter four seasons. UV–visible absorption and fluorescent spectroscopy were used to explore the optical characteristics of DOM. The results indicated a mixture of exogenous and autogenous sources of DOM in the Zhangxi watershed, while DOM in farmland exhibited a higher degree of aromaticity and humification than that in forestland. Fluorescent results showed that humic acid-like, fulvic acid-like and microbial-derived humic-like fractions were mostly affected by seasons. The distribution of heavy metals was affected mainly by land-use changes and seasons. Correlation analysis between heavy metals and DOM characteristics and components suggested that aromatic and humic substances were more favorable in binding with EDTA extractable Ni, Cu, Zn and Cd. The bioavailable Cd and Pb decreased due to binding with humic fractions, indicating its great effects on the bioavailability of Cd and Pb. Overall, these findings provide an insight into the correlative distributions of DOM and heavy metals in peri-urban areas, thereby highlighting their biogeochemical cycling in the soil environment. Graphical abstract: Image 1 Highlights: DOM in farmland showed a higher degree of aromaticity than that in forestland. The distribution of heavy metals extracted with different methods was explored. Humic fractions can reduce the bioavailability of Cd and Pb.